DIFFERENCES IN BANKING FINANCIAL PERFORMANCE BEFORE AND AFTER MERGER (CASE STUDY OF DOMESTIC BANKS IN INDONESIA) - Nyoman Sawitri, Ni (Green Publisher, 2022)
This study is to determine whether there are differences in the financial performance of banks before and after the merger as measured using the rasio of banking financial performance observation period of 2 years before and 2 years after the merger (2017-2021). The analytical method used in this research is descriptive analysis and the Paired Sample T test difference test to determine the difference with data that are normally distributed. The results of the descriptive analysis in this study showed an increase in the ratio of BOPO, CAR, and NPL, while the ratio of NIM, LDR, ROA, and ROE tended to decrease. The results of the Paired Sample T test at Bank Oke Indonesia showed that only the NPL ratio showed a difference between before and after the merger, while the results of the Paired Sample T test at Bank IBK Indonesia showed only the CAR and LDR ratios which showed a significant difference. between before and after the merger, as well as the results of the Paired Sample T test at Bank Danamon Indonesia showed that only the BOPO, ROA, and LDR ratios showed a difference between before and after the merger.